Relevansi Teori Multiple Intellegences dengan Undang-Undang Sistem Pendidikan Nasional Tahun 2003 - Mufrih Almunadi (Tadabbur: Jurnal Peradaban Islam, 2022)
Howard Gardner's idea about the existence of multiple intelligences or multiple intelligences which he outlined in his book "Frames of Mind" has changed the perspective of many people in studying human intelligence. To recognize and develop all the intelligences possessed by each student which varies greatly and all combinations of these intelligences the state has an important role to play, including in formulating various policies in education laws. However, in Indonesia, there are still many teachers who often do not provide opportunities and opportunities for their students to develop their multiple intelligences through suitable learning strategies and methods. One of the factors that may underlie this is the absence of mention of the theory of multiple intelligences in the Indonesian National Education System Law or the 2003 National Education System Law. In this study the authors wish to examine the relevance of the theory of multiple intelligences to the 2003 National Education System Law. This research is a qualitative research that can be categorized as library research. The results of this study explain that there is some relevance between the theory of multiple intelligences and the 2003 National Education System Law.